A Glimpse of Chinese-Malay Literature - Cendrawaty Tjong (Bina Nusantara University, 2007)
Chinese-Malay literature begans in the end of 19th century. The beginning of this period was known from the works depicted Classical-Malay literature. In the development, due to the booming of publication houses and newspaper agencies, this school of literature flourished. The origin of this period was closely related to Chinese-descendants, background and history. The long history, the big numbers of works and the miscellaneous contents of the works were the characteristics of this period. Chinese-Malay literature period was the period highlighted with typical Chinese-Indonesian society.